Răspuns :
Răspuns:
((6x3-3+3x3(3+1)) +3-1x3+3
(18-3+3x3x4)+3-3+3
(18-3+36)+3-3+3
51+3-3+3
51+3
54
9+8((7+6(5+12)-2)-10)-100
9+8((7+6x17-2)-10)-100
9+8((7+102-2)-10)-100
9+8(107-10)-100
9+8x97-100
9+776-100
685
Explicație pas cu pas:
orice expresie inmultita cu 1 ramane neschimbata
Răspuns:
Explicație pas cu pas:
o. [(3+3)×3-3+3×(3+3:3)]:3-3×3+3:3×1+3:1 =
[6×3-3+3×(3+1)]:3-9+1+3 =
(6×3-3+3×4):3-9+1+3 =
3×(6-1+4):3-9+1+3 =
3×9:3-9+1+3 =
1×9-9+1+3 =
9-9+1+3 =
1+3 =
= 4.
p.9+8×[7+6×(5+12)-2]-100 =
9+8×(7+6×17-2)-100 =
9+8×(7+102-2)-100 =
9+8×107-100 =
9+856-100 =
865-100 =
= 765.